1984
DOI: 10.1037/h0085984
|View full text |Cite
|
Sign up to set email alerts
|

The use of paradoxical interventions within a prison psychiatric facility.

Abstract: A brief history of paradoxical interventions and a rationale for applying paradoxical techniques to the cases of inpatients at a prison psychiatric facility are outlined. Common inmate personality characteristics and type of paradoxical techniques indicated are discussed. Four case studies are presented, as well as indications and contraindications for the utility of such interventions.An inpatient psychiatric hospital located within a prison setting often conjures up images of "mass murderers'" and "criminall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the case of an elderly couple who were spending increasingly less time together due to their frequent arguing, Gilewski, Kuppinger, and Zarit (1985) found that SP resulted in the couple spending more time together and arguing less. Chase, Shea, and Dougherty (1984), in their study of paradoxical interventions on prison inmates, commented that a wide range of pathological behavior may be resolved through SP. They also noted the beneficial impact such interventions can have on therapists, since these approaches help therapists avoid power struggles typically encountered with a prison population and make therapy less frustrating and more enjoyable.…”
Section: Symptom Prescriptionmentioning
confidence: 99%
“…In the case of an elderly couple who were spending increasingly less time together due to their frequent arguing, Gilewski, Kuppinger, and Zarit (1985) found that SP resulted in the couple spending more time together and arguing less. Chase, Shea, and Dougherty (1984), in their study of paradoxical interventions on prison inmates, commented that a wide range of pathological behavior may be resolved through SP. They also noted the beneficial impact such interventions can have on therapists, since these approaches help therapists avoid power struggles typically encountered with a prison population and make therapy less frustrating and more enjoyable.…”
Section: Symptom Prescriptionmentioning
confidence: 99%
“…Unfortunately, many case studies in which symptom prescriptions are utilized neglect these common clinical realities. Both controlled (e.g., Kolko & Milan, 1983) and uncontrolled (e.g., Chase et al, 1984; Haley, 1973) case studies frequently convey the impression that the removal of the target symptom resulted in the successful termination of treatment. Comparative treatment outcome studies (e.g., Michelson et al, 1985) also rarely report on the treatment of problems that are revealed during the course of therapy.…”
mentioning
confidence: 99%